Sustainable Design of Urban Stormwater Drainage Systems by Implementing Detention Tank and LID Measures for Flooding Risk Control and Water Quality Management - Li, Fei; Yan, Xu-Feng; Duan, Huan-Feng (Water resources management, 2019)
With the increasing emphasis and application of the flooding control and mitigation measures of detention tank (DT) and low impact development (LID) in urban stormwater drainage systems (USDSs), the complex drainage flow process and corresponding water quality issues have also aroused great of interests and attentions from researchers and practitioners. This paper contributes to study the urban flooding control and water quality management with the implementation of DTs and LIDs in the USDS. A many-objective optimization (MOO) based design framework and analysis method is developed for achieving four objectives of USDS design. A realistic USDS is adopted for the case study, in which the DTs and LIDs are implemented by this extended MOO-based design method to achieve the optimal result of flooding risk control and water quality improvement. The obtained results are further analyzed for the characteristics of flooding risk control and water quality component evolution in the USDS. The results and analysis demonstrate the effectiveness and applicability of the designed DTs and LIDs to mitigate the flooding risk and improve water quality in USDS.